2023
DOI: 10.3390/molecules28041791
|View full text |Cite
|
Sign up to set email alerts
|

Kinkéliba (Combretum micranthum) Leaf Extract Alleviates Skin Inflammation: In Vitro and In Vivo Study

Abstract: Kinkéliba (Combretum micranthum, Seh-Haw in Wolof) is a popular bush tea in West African countries. Although the kinkéliba plant’s leaves have been widely consumed for its nutritional and medicinal properties, its benefits on skin health potential have been practically untouched. In human epidermal primary keratinocytes, vitexin and isovitexin-rich kinkéliba extract treatment significantly (p < 0.001) enhanced up to 39.6% of the cell survival rate decreased by UV radiation irritation. The treatment of kinké… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Hu Shuting et al . (2023) validated in their study the ability of C. micranthum to reduce UV exposure generated by the pro‐inflammatory cytokines IL‐6/8 and to relieve skin inflammation [69] …”
Section: Pharmacological Activitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Hu Shuting et al . (2023) validated in their study the ability of C. micranthum to reduce UV exposure generated by the pro‐inflammatory cytokines IL‐6/8 and to relieve skin inflammation [69] …”
Section: Pharmacological Activitiesmentioning
confidence: 98%
“…[68] Hu Shuting et al (2023) validated in their study the ability of C. micranthum to reduce UV exposure generated by the proinflammatory cytokines IL-6/8 and to relieve skin inflammation. [69] 4.5. Antihypertensive Activity Seck et al (2017) showed the potential antihypertensive property of C. micranthum leaves.…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…For biological activities, fractions were tested at equivalent concentrations found in the crude extract, using in tubo assays for antioxidant and depigmenting properties (already reported in the literature for crude aqueous CM [19][20][21][22][23][24][25][26][27][28][29], and next, using in vitro cellular assays for anti-inflammatory activity [12] and collagen I synthesis, an activity never before reported for CM.…”
Section: Analyses Of In Tubo Biological Activitiesmentioning
confidence: 99%
“…No response for anti-inflammatory activity was observed for the butylene glycol CM extract or its kinkeloid enriched fraction; this anti-inflammatory activity is only observed for the aqueous CM-MO extract. This surprising response, given the literature on antiinflammatory activity and CM extracts, especially aqueous extracts [19][20][21][22][23][24][25][26][27][28][29], suggests three main hypotheses: Firstly, kinkeloids alone have no anti-inflammatory effect and require the highest presence of other components such as favonoids (found in the aqueous extract), as shown in Figure 5. Secondly, the possible antagonistic effect of the residual butylene glycol blank solvent on the expected anti-inflammatory response.…”
Section: Analyses Of Molecular Network and In Vitro Activitiesmentioning
confidence: 99%
See 1 more Smart Citation